The Place of Lifelong Learning in the Paidia Curriculum - Samira Heidari (Dinamika Ilmu, 2023)
Lifelong learning has become an important keyword in international research and studies because of its increasing impact on educational policies globally. One of the important goals of education systems worldwide is lifelong learning. The research method is descriptive-analytical. Data collection is in the form of extracting data from Adler's books, the second category of resources related to the Paidia curriculum. The method of data analysis was classification and interpretation, which was done simultaneously with data collection. In this descriptive-analytical study, Mortimer Adler's educational thinking has been analyzed in the context of Paideia, and the relationship between public education and continuous learning has been examined. According to the research findings, according to Adler, the public education curriculum underpins lifelong learning, and after school education, any failure in lifelong learning constitutes a failure in public education, while continuing learning. It can improve the health of students in adulthood. On the other hand, vocational education has no place in the Paideia curriculum. If, in the light of the critique of the plan, a stronger foundation for lifelong learning can be hoped for, given the place of work and profession in the field of public education. It is recommended that in future research, researchers compare Adler's perspective on continuous learning with other thinkers. One of the most important limitations of the current research was the lack of access to schools that were designed based on the Paidia program. Another suggestion for future research is to examine the schools that have been established based on the Paidia program and study the continuous learning process in them.